'It was dangerous, corrosive and cruel but not illegal': legal help-seeking behaviours amongst LGBTQA+ domestic and family violence victim-survivors experiencing coercive control in Australia - Reeves, Ellen (Journal of family violence, 2025)
Purpose: There is an expanding body of research interrogating lesbian, gay, bisexual, transgender, queer, asexual and other gender and sexuality diverse (LGBTQA+) persons’ experiences of domestic and family violence (DFV). However, few studies have considered LGBTQA+ persons’ specific experiences of ‘coercive control’ and none have considered legal help-seeking behaviours and decisions within this context. This article addresses this gap, through an examination of LGBTQA+ Australians’ experiences of legal help-seeking behaviours when experiencing coercive control from an intimate partner and/or family member. Method: The article draws on the qualitative responses of a sample of 137 LGBTQA+ victim-survivors who participated in a survey on Australians’ experiences of coercive control. The analysis considers the reasons why some participants did not report abuse to the police, and the impact of police reporting for those who did. Results: The study found that many of the concerns about the impact of reporting held by those who did not report to the police, were actualized in the experiences of those who did. Further, the study found that LGBTQA+ persons experience similar barriers to help-seeking compared to heterosexual and cisgender women, in addition to barriers that speak specifically to LGBTQA+ communities. Conclusion: The findings of this study highlight the shortcomings of the law’s response to domestic and family violence and the need for intersectional responses to coercive control in Australia and beyond. The emerging findings presented in this article reinforce the importance and further need for research that specifically examines LGBTQA+ experiences of coercive control.